2021
DOI: 10.3389/fmed.2021.656827
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Salmonellosis in Florida, USA, 2017–2018

Abstract: The state of Florida reports a high burden of non-typhoidal Salmonella enterica with approximately two times higher than the national incidence. We retrospectively analyzed the population structure and molecular epidemiology of 1,709 clinical isolates from 2017 and 2018. We found 115 different serotypes. Rarefaction suggested that the serotype richness did not differ between children under 2 years of age and older children and adults and, there are ~22 well-characterized dominant serotypes. There were distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…It seems that this serotype and/or S. Typhimurium are common nontyphoidal Salmonella spp. among Egyptians as reported in recent studies [40], which was also the case in Greece [41], Nigeria [42], and Florida (USA) [43]. In the present study, S. Apeyeme and S. Chester were identified in diarrheic and non-diarrheic patients, respectively, although they were not identified in animals.…”
Section: Discussionsupporting
confidence: 83%
“…It seems that this serotype and/or S. Typhimurium are common nontyphoidal Salmonella spp. among Egyptians as reported in recent studies [40], which was also the case in Greece [41], Nigeria [42], and Florida (USA) [43]. In the present study, S. Apeyeme and S. Chester were identified in diarrheic and non-diarrheic patients, respectively, although they were not identified in animals.…”
Section: Discussionsupporting
confidence: 83%
“…In previous investigations conducted in Iran, S. enterica serotype Enteritidis was found to be the most common serotype of Salmonella in people. Moreover, in a comprehensive study conducted in China, United States, and Taiwan, S. enterica serotype Enteritidis was the most prevalent strain serotype among human isolates (19)(20)(21)(22). These results are in agreement with our results, which revealed that S. enterica serotype Enteritidis was the predominant serotype.…”
Section: Discussionsupporting
confidence: 91%
“…The distribution of clusters of genetically related Salmonella isolates detected in our previous phylogenetic work [10] was consistent with the geographical pattern of areas with a highincidence rate of illness from varying serotypes. The hierarchical clusters based on cgMLST-clustered isolates were based solely on their genetic relatedness, without considering the spatial and temporal components in the data.…”
Section: Discussionsupporting
confidence: 88%
“…The five most common serotypes identified through the FoodNet surveillance system in the USA are Enteritidis, Typhimurium, Newport, Javiana and I 4, [5],12:i:-, a monophasic variant of Typhimurium [9], while the major serotypes occurring in Florida are Enteritidis, Newport, Javiana, Sandiego and Braenderup [6]. In our previous work, we conducted a phylogenetic analysis of Salmonella isolates from five dominant serotypes in Florida and identified the geographical distribution of clusters of genetically related isolates using core genome multi-locus sequence typing (cgMLST), a subtyping approach that provides high resolution to distinguish isolates within the same serotype [10]. Eight clusters of genetically related isolates from four serotypes (Enteritidis, Newport, I 4, [5],12:i:-and Bareilly) involved more than 10 isolates and were investigated.…”
Section: Introductionmentioning
confidence: 99%